Women and portraits in early modern Europe: Gender, agency and identity - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2009)
The Military Leadership of Matilda of Canossa is an important and welcome book.Although Matilda is readily acknowledged as a pivotal political figure of Italian,reform, and indeed even papal history in the eleventh and early twelfth centuries,she continues to be a rather poorly studied individual, especially in English-languagescholarship, despite the extensive range of primary sources for her life, including manydiplomata, which have recently been critically re-edited. At the same time, almost noattention has been given to Matilda’s military leadership, even though she was credited(and also censured) for her campaigns on behalf of the reforming papacy. Impeccablyresearched and cogently argued, this new book combines the acumen both of a militaryand a gender historian and sets an impressively high standard in terms of its contentand exposition.